Sensitivity of metastatic mucinous tailgut cyst adenocarcinoma to gemcitabine and radiation: a case report - Nusrat, Maliha; Yu, Kenneth H.; Tang, Laura; El Amine, Mohammad Ali; McCarthy, Brian; Ganesh, Karuna; de Stanchina, Elisa; Pappou, Emmanouil; Garcia-Aguilar, Julio; Bartelstein, Meredith; Crane, Christopher; Kelsen, David; et al. (Frontiers in Oncology, 2025)
Metastatic mucinous adenocarcinoma arising from a tailgut cyst is an ultra-rare cancer. Literature on the chemosensitivity and radiosensitivity of this cancer is lacking, and treatment is extrapolated from rectal cancer management. We are reporting, for the first time, the case of a patient with metastatic tailgut cyst adenocarcinoma who derived 1.5 years of clinical benefit from treatment with gemcitabine, selected as a result of transcriptomic analysis of her circulating tumor cells using an in vitro assay. The cancer was refractory to regimens extrapolated from rectal cancer management (capecitabine with oxaliplatin, and irinotecan). Pelvic recurrence and osseous metastases were clearly radiosensitive. Tumor molecular profile showed microsatellite stable cancer with KRAS p.G13D and TP53 p.C176W mutations.